FRI0284 Anti-Srp-Associated Autoimmune Myopathy: Younger Age at Onset Is Associated with More Severe Disease and Worse Outcome. (15th July 2016) - Pinal-Fernandez, I.; Parks, C.; Tiniakou, E.; Albayda, M.; Paik, J.; Lahouti, A.; Casal-Dominguez, M.; Pak, K.; Huang, W.; Lloyd, T.E.; Danoff, S.; Casciola-Rosen, L.; et al.
Abstract : Background: Anti-SRP autoantibodies are associated with an immune-mediated necrotizing myopathy. Although some anti-SRP-positive patients respond well to therapy, others continue to have active disease and persistent weakness despite treatment 1, 2 . Objectives: Here, we studied a large cohort of anti-SRP-positive patients to identify factors associated with disease severity and clinical improvement. Methods: All anti-SRP positive patients in the Johns Hopkins Myositis Cohort from 2002 to 2015 were included in the study. Longitudinal information regarding proximal muscle strength, creatine kinase levels, and immunosuppressive therapy were recorded at each visit. Univariate and multivariate analyses using multilevel regression models were used to assess prognostic factors influencing the recovery of strength over time. Results: Thirty-seven anti-SRP-positive patients (78% female) were included. Older age at onset was associated with greater strength at the first visit (p=0.02) and at all subsequent visits (p=0.002) independent of sex, race, disease duration and immunosuppressive treatment. Younger patients had worse outcomes, with less strength at the last visit (p=0.003) independent of disease duration, sex, and race. Although we could not definitively study response to treatment in this longitudinal cohort, rituximab appeared to be effective in 13 of 17 patients who received it (76%, 95%CI: 53% 90%). Younger patients often required continuous and intensive therapy with multiple immunosuppressive drugs to sustain full strength even two years after the onset of the disease. Conclusions: In anti-SRP-associated myositis, a younger age at disease onset is associated with more severe weakness and worse outcomes. Rituximab may be an effective treatment in both young and old patients. References: Suzuki S, Nishikawa A, Kuwana M, Nishimura H, Watanabe Y, Nakahara J, et al. Inflammatory myopathy with anti-signal recognition particle antibodies: case series of 100 patients. Orphanet J Rare Dis 2015;10:61. Casciola-Rosen L, Mammen AL. Myositis autoantibodies. Curr Opin Rheumatol 2012;24:602–8. Disclosure of Interest: None declared